LEADER SCHOOL: A MODERN LEADERSHIP AND MANAGEMENT MODEL - Mahmudov Bahriddin Jo’rayevich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The article analyzes the theoretical and practical aspects of the “Leader School” modern management school, established under the Faculty of Business Management at Namangan State Technical University. The study highlights the role of the school in developing students’ leadership qualities, strategic thinking, management skills, teamwork abilities, and innovative decision-making competencies. It also evaluates the contribution of “Leader School” to training competitive specialists through modern educational technologies, enhancing the managerial potential of youth, and fostering human capital development.